An original computer program (MalaxAction 1.0) to design and control olive paste malaxation under exposure to air. (October 2018) - Zanoni, B.; Breschi, C.; Canuti, V.; Guerrini, L.; Masella, P.; Picchi, M.; Parenti, A.
Abstract: An original computer program was set up to predict and control olive paste malaxation in the range of temperature between 22 and 37 °C under exposure to air. The program consisted of four sections to solve the our previous literature time-temperature kinetics. It was able to predict both the apparent oil extraction yield and the relative variation of 3, 4 DHPEA-EDA and sum of verbascoside diastereoisomers contents in steady and unsteady-conditions; it was also able to determine optimal malaxation time-temperature conditions to maximize the oil extraction yield and minimize the oxidative degradation of phenolic compounds. Simulation examples were carried out to test prediction potentiality. The malaxation treatments at low temperatures appeared preferable, since they seemed to be unaffected by time-temperature profiles under unsteady-state conditions. However, it seemed more difficult to identify optimal time-temperature conditions at a low temperature than at a high temperature in some operating states. Highlights: An original computer program was written to optimize olive paste malaxation under exposure to air. Simulation examples were carried out to predict oil yield and damage to phenols. Malaxation at low temperature and intermediate time appeared preferable. Some operating states appeared critical to identify optimal conditions.